KEBIJAKAN UU NO 1 TAHUN 2022 MENGENAI PERIMBANGAN KEUANGAN ANTAR PUSAT DAN DAERAH PASCA REFORMASI - Ifa, Siti Hudza; Pratama, Rizky; Arwanto, Bambang (Lex Journal: Kajian Hukum & Keadilan, 2022)
After the amendment, Regulation Number 25 of 1999 concerning Financial Balance between the Center and the Regions, but after the amendment of Regulation Number 33 of 2004 concerning Financial Balance between the Center and the Regions, the allocation of asset adjustments has moved to the dispersion of some normal assets in the area . The issue studied is where regional finance can increase and find sources of income which are expected to complement its independence as a result of the implementation of decentralization guidelines as adopted by the 1945 Constitution. The exploration technique used is essential literature studies, selected regulations and materials. tertiary legal materials, and the examination carried out is subjective standardization. With the issuance of the regulation on Fiscal Balance between the Center and the Regions after the amendment, it shows very large results for the implementation of provincial independence, considering that regional supporting sources are generally not solely based on PAD (Regional Revenue) results, but the regions also have different sources of initial funding from the regions, formerly only enjoyed by the central government. Keywords: Policy, Regional Finance, Post Reform